(untitled) (Acta Scientiarum. Health Sciences, 2020)
This study aimed to learn about the conditions of access to health services that seniors living in rural areas have, as well as their satisfaction. This is a qualitative, descriptive and exploratory research conducted in a municipality located in the southern region of Rio Grande do Sul, Brazil. It included 19 elderly individuals registered in three Basic Health Units organized in the form of Family Health Strategy. Data were collected between July and August 2018 through semi-structured interviews, which were analyzed based on Minayo’s operational proposal. Afterwards, two categories were defined: "Access to health services used by elderly residents of rural areas" and "Satisfaction with health services used by elderly residents of rural areas". Concerning access, many are the difficulties faced, such as long distances to be traveled until arriving at a health service, poor road conditions, limitations related to public transport days, timetables and itineraries, lack of human and material resources, and long waiting time to make appointments with specialists and schedule exams through the Brazilian Unified Health System. As for satisfaction, the main complaint of the elderly participants refers to issues involving, above all, health management and work process, such as delay in making health care appointments, although most participants reported being satisfied with the care provided by health professionals. It is worth noting that learning about the conditions of access to health services used by elderly people living in rural areas and their satisfaction contributes to the planning, implementation, development and evaluation of public health actions, programs and policies.